Relationship Between Student Characteristics and Handwashing Habit with Worm Disease Incidence in Islamic Boarding School Blitar District - Aida Erna M; J Mukono (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Worm  disease incidence in islamic  boarding  school can  be influenced by  student characteristics and handwashing habit. Student characteristics were cocidered into age and lived period  in islamic boarding school. Hand washing were  seen from handwashing habit  before ate  and after defecation. Purpose of this  study  was  to analyze relationship  between student characteristics and handwashing habit with worm disease incidence in islamic boarding school. This study was observational analytic study with cross sectional design. Student characteristics and handwashing habit data were  obtained questionnaires by 71 students. Worm disease incidence was  known  from laboratory testing of student feces. Worm disease incidence in islamic  boarding school were  2.8% with worm species were  Enterobius vermicularis  and Hookworm. Results of data collection were  analyzed using  Chi Square test with value  of α =  0.05. Student characteristics showed most  student was  16 years old and live in boarding  school for 1 year. Hand washing habit student islamoc boarding  school before eating was bad and after defecation was good. There was a relationship between live period  in islamic  boarding  school (p =  0.016),  handwashing habit before eating  (p =  0.008)  and  after defecation (p  =  0.018)  with worm  disease incidence. There  was  no  relationship between age  and  worm  disease incidence (p =  0.205).  Student islamic boarding  school should improve  handwashing habit before eating  and  after defecation used soap  and running water.Keywords: student islamic  boarding  school  characteristics, handwashing habit,  worm  disease, islamic  boarding school